2022
DOI: 10.5194/bg-19-4655-2022
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas fluxes from tidal salt marsh soils: implications for carbon–sulfur biogeochemistry

Abstract: Abstract. Tidal salt marsh soils can be a dynamic source of greenhouse gases such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), as well as sulfur-based trace gases such as carbon disulfide (CS2) and dimethylsulfide (DMS) which play roles in global climate and carbon–sulfur biogeochemistry. Due to the difficulty in measuring trace gases in coastal ecosystems (e.g., flooding, salinity), our current understanding is based on snapshot instantaneous measurements (e.g., performed during daytime lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 91 publications
0
37
0
Order By: Relevance
“…In addition to understanding the physical and chemical controls on horizontal C transport, it is also essential to know how soil trace gas emissions change across tidal cycles (Capooci & Vargas, 2022b). Fluxes of soil greenhouse gases (e.g., CO 2 , CH 4 ) offset the global cooling effect of stored C in soil.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to understanding the physical and chemical controls on horizontal C transport, it is also essential to know how soil trace gas emissions change across tidal cycles (Capooci & Vargas, 2022b). Fluxes of soil greenhouse gases (e.g., CO 2 , CH 4 ) offset the global cooling effect of stored C in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Second, soil GHG fluxes could present hot moments, which are transient events with disproportionately high values that are often missed with an FTS approach (Vargas et al, 2018;Butterbach-Bahl et al, 2004). Third, cumulative sums and uncertainty ranges are biased or misleading when derived using an FTS approach (Tallec et al, 2019;Lucas-Moffat et al, 2018;Capooci and Vargas, 2022b). Our study demonstrates that an optimized approach consistently provided closer estimates for cumulative sums and uncertainty ranges when compared with automated measurements (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Automated measurements have revolutionized our understanding of the temporal patterns and magnitudes of soil GHG fluxes (Savage et al, 2014;Bond-Lamberty et al, 2020;Tang et al, 2006;Capooci and Vargas, 2022b). These measurements have limitations in representing spatial variability and have higher equipment costs that limit their broad applicability across study sites (Vargas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that P, K, and Na appear to play an important role in increasing F A among all categories (i.e., ecosystem scale, S. alterniflora , and S. cynosuroides ), while an increase in Fe had a negative effect on F A . The influence of N and S on F A was more variable among vegetation categories (Figure 7), suggesting confounding effects with local sediment biogeochemistry that varies across the marsh (Capooci & Vargas, 2022b; Seyfferth et al., 2020). Other nutrients such as Cu and Si that are important for plant growth of Spartina spp.…”
Section: Discussionmentioning
confidence: 99%